Pressure control cam displacement in the Codman-Hakim programmable valve after a 3T MRI: Case report and review of the literature - Jose A. Castillo, Jr, MD; Khadija Soufi, BA; Anzhela Moskalik, MD; Arash Ghaffari-Rafi, MD; Edwin Kulubya, MD; Claire Basco, NP; Kia Shahlaie, MD, PhD; Marike Zwienenberg, MD (Radiology Case Reports, 2023)
Pressure control cam dislocation is a rare finding in patients with a programmable shunt valve that should be considered when evaluating patients with signs and symptoms of shunt malfunction. The objective of this paper is to review the mechanism, clinical presentation, and radiographic findings associated with pressure control cam (PCC) dislocation, in addition to presenting a novel case to add to the scarce literature on this topic. A systematic review of the literature were performed using PubMed, Embase, and Cochrane from database inception. PCC dislocation is exceedingly rare and can present with no symptoms, positional headache, neck pain, nausea, or vomiting. Skull x-ray findings demonstrate a clear black “X” at the distal end of the valve, due to the PCC disarticulation from atop the base plate of the plastic valve housing. Intraoperatively, a “Y”-shaped crack atop the plastic valve housing may be present and the PCC may be fully separated from the shunt or found at the distal end of the plastic valve housing. Prior reports of dislocation of the PCC have occurred 7-9 years after implantation, with inciting events including direct trauma, programmable valve adjustment, and utilization 3-Tesla magnetic resonance image scan.